2021
DOI: 10.1186/s12887-021-02933-4
|View full text |Cite
|
Sign up to set email alerts
|

Screening for post-traumatic stress disorder among adolescents following floods- a comparative study from private and public schools in Kerala, India

Abstract: Introduction Disasters can have deep physical and psychological impact among survivors. An extraordinary southwest monsoon has unleashed floods and landslides in Kerala state in 2018. Adolescents are more vulnerable to psychological impairment after a disaster and trauma during initial stages of life can etch an indelible signature in the individual’s development and may lead to future disorders. Objectives 1. To screen for PTSD and associated fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…Facing a disaster of this magnitude would be a different experience for the landslide survivors. These results are consistent with the findings of the study conducted in India among adolescents following floods [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…Facing a disaster of this magnitude would be a different experience for the landslide survivors. These results are consistent with the findings of the study conducted in India among adolescents following floods [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, the present study showed in pre-test, a high proportion (34-80) of PTSD among adolescents 27 (32.5%) and in post-test, a high proportion (0-33) of PTSD among adolescents 40 (100%) who experienced flood. Reviewing literature, a similar study done by Geethu et al in Alleppey district of Kerala, India showed a high proportion of PTSD (34.9%) among adolescents even after 8 months post disaster who experienced flood 11 . One more similar study done by Deiveegan C et al in Uttarakhand, India, showed that the prevalence of PTSD by the TSQ was found to be 86 (67.7%) among victims 7 .…”
Section: Discussionmentioning
confidence: 73%
“…An earlier study on PTSD in flood survivors of Kerala flood 2018 highlighted the need to carry out post-disaster mental health screening because of the high prevalence of PTSD following the floods [ 16 ]. Similarly, another study revealed that even eight months post disaster, a sizable percentage of adolescents were still experiencing stress-related disorders [ 15 ]. The health department of Kerala trained close to 1000 volunteers to help affected flood victims.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, such natural disaster may have huge impact on the mental wellbeing of the victims and therefore, exploration of psychological effects on survivors is important to develop coping strategies. Though few studies have reported the prevalence of PTSD among adolescents [ 15 ] and adults [ 16 ] of 2018 flood victims in Kerala, there are no reports available on other associated psychological disorders such as depression and anxiety. Therefore, we assessed the relationship between the socio-economic and flood exposure factors with PTSD, depression and anxiety among the flood survivors in the Kozhikode district of Kerala, India.…”
Section: Introductionmentioning
confidence: 99%